2009
DOI: 10.1590/s1516-89132009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between seminal malondialdehyde levels and sperm quality in fertile and infertile men

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 30 publications
2
18
2
Order By: Relevance
“…Malondialdehyde (MDA) level of BAL fluid was assessed using the thiobarbituric acid method (TBAR) method (Colagar et al, 2009;Layali et al, 2015;Rao et al, 1989). Briefly, 5 ml of BAL fluids were centrifuged for 7 min at 2000g and then 100 l of supernatants was added in 900 l of distilled water into a glass tube.…”
Section: Mda Measurementmentioning
confidence: 99%
“…Malondialdehyde (MDA) level of BAL fluid was assessed using the thiobarbituric acid method (TBAR) method (Colagar et al, 2009;Layali et al, 2015;Rao et al, 1989). Briefly, 5 ml of BAL fluids were centrifuged for 7 min at 2000g and then 100 l of supernatants was added in 900 l of distilled water into a glass tube.…”
Section: Mda Measurementmentioning
confidence: 99%
“…ROS and RNS (e.g., H 2 O 2 , O 2 , and NO) are particularly reactive oxidizing factors, which are among free radicals reacting with macromolecules for compensation of their electron deficit (12). They can oxidize macro-molecules such as polyunsaturated fatty acids (PUFA), proteins, and carbohydrates (13).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation (LPO) is the main pathological effect of free radicals, correlated with PUFA oxidation in the sperm membranes (13). Malondialdehyde (MDA) is a steady byproduct of PUFA oxidation, which can be measured as a diagnostic index of sperm lipid peroxidation (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies improved that defective sperm function is associated with the presence of ROS in the seminal fluid, in which produced from many sources, and suggested that the ROS negatively correlated with sperm count, sperm motility and sperm morphology [12,13].…”
Section: Introductionmentioning
confidence: 99%